Automatización de la Jaula de Faraday para la seguridad de maniobras en el laboratorio de alto voltaje en la carrera de Ingeniería Eléctrica de la Universidad Técnica de Cotopaxi. - Pérez Guilcaso, Edgar Mauricio (2021)
This project developed as a technological proposal was implemented in the high voltage laboratory of the Technical University of Cotopaxi (Faculty of Engineering and Applied Sciences) From the design of the control system used programmable logic modules to automate the Faraday Shield. The design has a motion control system activated by a PLC S7 1200, through the TIA Portal software, the PTO impulse train signals were programmed to the drives that drive the stepper motors, necessary for the movement of the pulley system to control the movement on a y axis (vertical movement), x (horizontal movement) and z (front movement) the position of the grounding wire. In addition, a safety control system was installed in the presence of High Voltages through a LOGO 230RC, whose programming was developed in the Soft Comfort software executing output signals electrometric turbine siren, flashing warning lights, and the interlock system that controls the power supply. to the control mode of the High Voltage transformer, as well as the ignition drive for the motion control system, to guarantee the safety of maneuvers during tests carried out in the Faraday Shield. The main methodology applied in this proposal was experimental, technical, and normative guides associated with the development of this project were used. The automation system has been validated through tests, calibrations, and operation manuals of the control systems, at the same time the performance of dielectric breakdown tests, to verify the correct operation of the control modules in the Faraday Shield.